PAM / COF composite material for treating dye wastewater and preparation method of PAM / COF composite material

The PAM/COF composite material prepared by emulsion polymerization solves the problems of low mechanical strength and low adsorption efficiency in dye wastewater treatment, and achieves efficient and stable dye wastewater treatment and has good regeneration performance.

CN119735282AActive Publication Date: 2025-04-01TARIM UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510096001.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-01
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing covalent organic framework (COF) materials have problems such as low mechanical strength, poor dispersion, easy agglomeration, low adsorption efficiency, and poor regeneration performance in dye wastewater treatment.

Method used

Porous polyacrylamide (PAM) material is prepared by emulsion polymerization, and combined with COF material to form PAM/COF composite material to enhance its mechanical strength and adsorption properties.

Benefits of technology

PAM/COF composites significantly improve adsorption efficiency when treating dye wastewater, maintain good mechanical strength and chemical stability, can maintain excellent adsorption capacity at a wide pH range and different temperatures, and have good regeneration performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735282A_ABST
    Figure CN119735282A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wastewater treatment, and particularly relates to a PAM / COF composite material for treating dye wastewater and a preparation method of the PAM / COF composite material. The preparation method comprises the following steps: dissolving p-toluenesulfonic acid monohydrate and trialdehyde phloroglucinol into deionized water to obtain a mixed solution A, and ultrasonically dispersing acrylamide, N, N-methylene bisacrylamide, polyvinylpyrrolidone, PEG-200 polyethylene glycol and Tween 20 into the deionized water to obtain a water phase; mixing benzene, n-heptane and cyclohexane according to a volume ratio of 1: 1: 2.5 to obtain an oil phase; the preparation method comprises the following steps: preparing PAM powder by adopting an emulsion polymerization mode, adding the PAM powder into a mixed solution A, then adding diamino-anthraquinone, mixing, carrying out a heating reaction, and then drying to obtain the PAM / COF composite material. The PAM / COF composite material is prepared from an organic framework (COF) material and polyacrylamide (PAM), and the problems that the COF material is low in mechanical strength, poor in dispersity, prone to agglomeration, low in adsorption efficiency, poor in regeneration performance, poor in complex dye wastewater treatment effect and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to a PAM / COF composite material for treating dye wastewater and a preparation method thereof. Background Art

[0002] The rapid development of the textile industry has produced a large amount of dye wastewater. The composition of dye wastewater is complex, containing organic matter and harmful substances, and it is highly toxic. The water body cannot degrade pollutants in a short time through simple self-purification. This will not only cause harm to the water body and aquatic organisms, but will also continue to accumulate along the food chain, and ultimately threaten human health. Commonly used treatment methods for dye wastewater include biological method, membrane separation method, photocatalytic method, electrochemical method, adsorption method, etc. Among them, the adsorption method has the advantages of simple operation, high efficiency, and low cost, and is widely used to treat dye wastewater.

[0003] In recent years, covalent organic framework (COF) materials, as a new type of porous material, have attracted the attention of researchers due to their unique adjustable structure, large specific surface area and excellent adsorption performance. COF materials can physically or chemically interact with dye molecules through their ordered pore structure, thereby achieving efficient adsorption. However, COF materials also have certain limitations in practical applications, such as low mechanical strength, poor dispersibility, and easy agglomeration, which limits their use in water treatment. Summary of the invention

[0004] The purpose of the present invention is to provide a PAM / COF composite material for treating dye wastewater and a preparation method thereof, aiming to overcome the problems of low mechanical strength, poor dispersibility, easy agglomeration, low adsorption efficiency, poor regeneration performance, and poor dye wastewater treatment effect of covalent organic framework (COF) materials in the prior art.

[0005] The present invention is specifically implemented by the following technical scheme. According to the present invention, a preparation method of a PAM / COF composite material for treating dye wastewater comprises the following steps: (1) Weigh a certain amount of p-toluenesulfonic acid monohydrate and trialdehyde phloroglucinol, add them to deionized water, and ultrasonically vibrate for 10-20 min to obtain a mixed solution A; (2) Taking a certain volume of deionized water, add acrylamide, N,N-methylenebisacrylamide, polyvinyl pyrrolidone, PEG-200 polyethylene glycol and Tween 20 in sequence, and disperse by ultrasonic until the mixture is completely dispersed to obtain an aqueous phase; (3) mixing benzene, n-heptane and cyclohexane in a volume ratio of 1:1:2.5 and stirring well to obtain an oil phase; (4) According to the volume ratio of water phase to oil phase of 2:1, a certain amount of water phase prepared in step (2) and oil phase prepared in step (3) are taken, and the oil phase is added to the water phase while stirring. After the oil phase is completely added, stirring is continued until a milky white oil-in-water emulsion is formed, and ammonium persulfate is added to the oil-in-water emulsion. After stirring, the mixture is transferred to a polytetrafluoroethylene-lined reactor, and then N,N,N',N'-tetramethylethylenediamine is dropped into the polytetrafluoroethylene-lined reactor and quickly stirred. Subsequently, the polytetrafluoroethylene-lined reactor is sealed and placed in an oven at 55°C for reaction for 8-20 min. After the reaction is completed, the obtained product is centrifuged and washed three times with methanol, and then the centrifuged product is dried in a vacuum oven at 50°C for 8-12 h to obtain a porous polyacrylamide powder, which is recorded as PAM powder. (5) Add the prepared PAM powder to the mixed solution A of step (1) and stir evenly to obtain a mixed solution B; add diaminoanthraquinone to the mixed solution B, stir evenly and transfer to a polytetrafluoroethylene-lined reactor, heat the polytetrafluoroethylene-lined reactor at 120° C. for 18 h to fully react, and after the reaction is completed, naturally cool the product to room temperature and then vacuum dry to obtain a porous polyacrylamide / COF composite material, recorded as PAM / COF composite material.

[0006] In the aforementioned preparation method of the porous polyacrylamide / COF composite material for treating dye wastewater, the mass ratio of p-toluenesulfonic acid monohydrate to trialdehyde phloroglucinol is 22:5, and the ratio of the volume of deionized water to the total mass of p-toluenesulfonic acid monohydrate and trialdehyde phloroglucinol is 8 mL: 27 mg.

[0007] The method for preparing the porous polyacrylamide / COF composite material for treating dye wastewater is as follows: in step (2), the mass ratio of acrylamide, N,N-methylenebisacrylamide, polyvinyl pyrrolidone, PEG-200 polyethylene glycol, and Tween 20 is 13:1:1:1.2:8; and the volume ratio of the deionized water in step (2) to the volume ratio of the deionized water in step (1) is 1:1.

[0008] In the aforementioned method for preparing the porous polyacrylamide / COF composite material for treating dye wastewater, the stirring speed in step (4) is 1500 rpm.

[0009] In the aforementioned method for preparing a porous polyacrylamide / COF composite material for treating dye wastewater, in step (4), the concentration of ammonium persulfate in the water-in-oil emulsion is 1.25 mg / mL, and the volume ratio of N,N,N',N'-tetramethylethylenediamine to the volume of the water-in-oil emulsion is 1:120.

[0010] In the aforementioned method for preparing the porous polyacrylamide / COF composite material for treating dye wastewater, the mass ratio of diaminoanthraquinone in step (5) to trialdehyde phloroglucinol in step (1) is 3:5.

[0011] In the aforementioned method for preparing a porous polyacrylamide / COF composite material for treating dye wastewater, the PAM powder prepared in step (4) is a nearly spherical particle with a particle size of 300-600 μm; in the PAM / COF composite material prepared in step (5), the COF material is attached to the pore structure of the PAM material, and the particle size of the COF material is 50-200 nm.

[0012] The present invention also provides a PAM / COF composite material obtained according to the preparation method and its application in treating dye wastewater. The PAM / COF composite material is added to the dye wastewater for oscillation adsorption. After 90 to 120 minutes, the adsorption reaches equilibrium.

[0013] Preferably, the pH of the dye wastewater is greater than 7, the concentration thereof is 30-50 mg / L, and the volume ratio of the added mass of the PAM / COF composite material to the dye wastewater is 3 mg: 10 mL.

[0014] Furthermore, the dye includes but is not limited to methyl orange, Congo red, methylene blue, and crystal violet.

[0015] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages: (1) The present invention uses emulsion polymerization to prepare porous polyacrylamide (PAM) material. Polyacrylamide (PAM) is a polymer material with good adsorption capacity. Its structure contains a large number of functional groups, which can strongly react with pollutants in water, thereby effectively removing pollutants in water. The organic framework (COF) material and polyacrylamide (PAM) are prepared into PAM / COF composite materials, which can overcome the defects of poor mechanical properties of COF materials and enhance the overall adsorption performance of the composite materials. In particular, the nearly spherical porous structure of polyacrylamide not only improves the mechanical strength of the material, but also the COF material is attached to the pore structure of the porous polyacrylamide (PAM), which helps to reduce or avoid the agglomeration of the COF material, so that the PAM / COF composite material shows good structural stability during long-term use, avoiding the problem of easy agglomeration and poor dispersibility of traditional COF materials in water environment. In addition, the spherical porous structure of PAM enhances the compressive resistance of the composite material, so that it will not be significantly broken or deformed during long-term wastewater treatment, thereby extending the service life of the composite material.

[0016] (2) The PAM / COF composite material prepared by the present invention has a large specific surface area and a rich pore structure, which can significantly improve the adsorption efficiency and has excellent chemical and mechanical stability. It has a significant adsorption effect on methyl orange dye wastewater. In a wide pH range (such as from acidic to neutral) and at different temperatures (such as room temperature to high temperature), the PAM / COF composite material can maintain excellent adsorption capacity and is less affected by environmental conditions, thereby improving its applicability in practical applications.

[0017] (3) The PAM / COF composite material of the present invention not only has an excellent adsorption effect on methyl orange dye wastewater, but also exhibits good adsorption performance on other common dyes (such as methylene blue, Congo red, etc.). Therefore, the PAM / COF composite material prepared by the present invention is suitable for treating various types of dye wastewater and has broad application prospects in the textile, printing and dyeing and other industrial fields.

[0018] (4) The PAM / COF composite material prepared by the present invention has good mechanical strength and chemical stability, and can achieve regeneration of the adsorption material by simple alkaline washing. The regeneration operation is convenient, which reduces the consumption and cost of materials and improves the economic benefits. It can maintain good adsorption performance during multiple regeneration cycles. During multiple regeneration cycles, the PAM / COF composite material will not be significantly broken or deformed, indicating that the PAM / COF material has good stability and a long service life, and can effectively reduce the operating cost of industrial wastewater treatment. At the same time, the efficient adsorption capacity of the PAM / COF composite material can accelerate the wastewater treatment speed, improve the treatment efficiency, and enhance the economic benefits of the entire wastewater treatment process.

[0019] (5) The preparation method of the present invention is simple, the cost of raw materials is low, the preparation conditions are mild, and it is easy to operate. The prepared PAM / COF composite material has both high durability and regeneration ability, which can reduce the overall production and use costs of the adsorption material and improve production efficiency and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 1 is a scanning electron microscope image of the PAM powder prepared in Example 1 at different magnifications.

[0021] Figure 2 is a scanning electron microscope image of the PAM / COF composite material prepared in Example 1.

[0022] Figure 3 This is the curve of the adsorption efficiency of methyl orange by PAM material and PAM / COF composite material changing with the adsorption time.

[0023] Figure 4This is the curve of the adsorption efficiency of methyl orange of PAM / COF composite material changing with adsorption time at different temperatures.

[0024] Figure 5 This is the curve of the adsorption efficiency of PAM / COF composite material for methyl orange aqueous solution with different pH values ​​as a function of adsorption time.

[0025] Figure 6 This is the curve of the adsorption efficiency of PAM / COF composite materials for different dyes changing with adsorption time.

[0026] Figure 7 This is a comparison chart of the adsorption efficiency of PAM / COF composite materials on methyl orange aqueous solution under different adsorption cycles. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present invention is described in detail with specific examples below. If no specific conditions are specified in the following examples, they are all carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials and reagents used without specifying the manufacturer are all conventional products that can be purchased from the market.

[0029] Example 1 (1) Weigh 220 mL of p-toluenesulfonic acid monohydrate and 50 mg of trialdehyde phloroglucinol, add them to 80 mL of deionized water, and ultrasonically vibrate for 10 min to obtain a mixed solution A.

[0030] (2) Take another 80 mL of deionized water and add 13 g acrylamide, 1 g N,N-methylenebisacrylamide, 1 g polyvinyl pyrrolidone, 1.2 g PEG-200 polyethylene glycol and 8 g Tween 20 in sequence. Disperse by ultrasonication until the mixture is completely dispersed to obtain an aqueous phase.

[0031] (3) Mix 10 mL of benzene, 10 mL of n-heptane, and 25 mL of cyclohexane (the volume ratio of benzene, n-heptane, and cyclohexane is 1:1:2.5), stir thoroughly, and obtain an oil phase.

[0032] (4) Stir the aqueous phase of step (2) at a speed of 1500 rpm, and add 40 mL of the oil phase prepared in step (3) while stirring. After the oil phase is completely added, continue to stir at a speed of 1500 rpm until a milky white water-in-oil emulsion is formed, and the final volume ratio of the water phase to the oil phase is 2:1. Then add 150 mg of ammonium persulfate to the obtained water-in-oil emulsion, stir evenly, and transfer the mixed solution to a polytetrafluoroethylene-lined reactor. Drop 1 mL of N,N,N',N'-tetramethylethylenediamine into the polytetrafluoroethylene-lined reactor and stir quickly to make it even; then seal the polytetrafluoroethylene-lined reactor and place it in an oven at 55°C for 8 min. After the reaction is completed, the obtained product is centrifuged and washed three times with methanol, and then the centrifuged product is dried in a vacuum oven at 50°C for 8 h to obtain a porous polyacrylamide powder, which is recorded as PAM powder.

[0033] (5) Add the prepared PAM powder to the mixed solution A in step (1) and stir evenly to obtain a mixed solution B; add 30 mg of diaminoanthraquinone to the mixed solution B, stir evenly and transfer to a polytetrafluoroethylene-lined reactor, place the polytetrafluoroethylene-lined reactor in an oven and heat at 120°C for 18 h to fully react. After the reaction is completed, the product is naturally cooled to room temperature and then vacuum dried at a drying temperature of 65°C for 18 h. After drying, a porous polyacrylamide / COF composite material is obtained, which is recorded as a PAM / COF composite material.

[0034] The surface morphology of the PAM powder and PAM / COF composite material prepared in Example 1 was observed by scanning electron microscopy. Figure 1 and Figure 2 shown.

[0035] Figure 1 (a) is a scanning electron microscope image of the PAM powder prepared in Example 1 at a magnification of 800 times. Figure 1 (b) is a scanning electron microscope image of the PAM powder prepared in Example 1 at a magnification of 2500 times. Figure 1 In (a), we can see that the PAM powder is a nearly spherical particle with a particle size of about 300-600 μm. Figure 1 In (b), it can be observed that the surface of the PAM particles is distributed with pore structures of uneven sizes, including nanoscale pores and microscale pores. Therefore, PAM has a porous structure.

[0036] Figure 2This is a scanning electron microscope image of the PAM / COF composite material prepared in Example 1. It can be clearly seen that the COF material is attached to the pore structure of the porous polyacrylamide (PAM), and the particle size of the COF material is about 50-200 nm.

[0037] Test on the adsorption effect of PAM / COF composite materials on dye wastewater: 1. Comparison of adsorption effects of PAM powder and PAM / COF composites 15 mg of the PAM powder prepared in step (4) of Example 1 and the PAM / COF composite material prepared in step (5) were weighed and placed in two beakers respectively. 50 mL of a 30 mg / L methyl orange aqueous solution was added to the two beakers, and the mixture was placed in a constant temperature oscillator for oscillation adsorption at room temperature. A certain amount of the solution was taken at regular intervals, and after centrifugation, the supernatant was taken and the absorbance was tested using a TU-1901 UV-visible photometer. The absorbance was substituted into the standard curve equation of the change of methyl orange absorbance with concentration to obtain the concentration of methyl orange corresponding to the corresponding absorbance. The adsorption efficiency was calculated according to the following formula (1): q t =(( c 0 - c t ) / c 0 )×100% (1) In the formula, q t represents the adsorption efficiency, c 0 represents the initial concentration of methyl orange aqueous solution, unit: mg / L; c t Represents the concentration of methyl orange aqueous solution at time t, unit: mg / L.

[0038] Plot the adsorption efficiency as the ordinate and the adsorption time as the abscissa, such as Figure 3As shown in the figure, it can be seen that within the first 20 min, both the PAM material and the PAM / COF composite material showed a faster adsorption rate. This is because the dye concentration was high in the initial stage, and there were a large number of active sites on the surface of the material, which rapidly adsorbed the dye molecules. During the entire adsorption process, the adsorption efficiency of the PAM / COF composite material for methyl orange was significantly higher than that of the PAM material. At 60 min, the adsorption efficiency of the PAM / COF composite material for methyl orange was close to 90%, while the adsorption efficiency of the PAM material for methyl orange was close to 70%. This difference is attributed to the addition of the COF material, which enhanced the porosity and specific surface area of ​​the PAM / COF composite material and provided more adsorption sites for the dye molecules. At about 100 min, the PAM / COF composite material basically reached adsorption equilibrium, and its adsorption efficiency for methyl orange exceeded 90%. In contrast, the adsorption efficiency of the PAM material for methyl orange in the same time was only about 80%. This shows that the introduction of the COF material significantly improved the adsorption performance and adsorption rate of the PAM / COF composite material, and the adsorption equilibrium time of the PAM / COF composite material for methyl orange was 100~120 min.

[0039] (II) Comparison of adsorption effects of PAM / COF composites on methyl orange at different temperatures 15 mg of PAM / COF composite material was added to 50 mL of 30 mg / L methyl orange aqueous solution, and placed in a constant temperature oscillator for oscillation adsorption at 20°C. A certain amount of solution was taken at regular intervals, and the supernatant was taken after centrifugation to test the absorbance of the solution using a TU-1901 UV-visible photometer. The absorbance was substituted into the standard curve equation of the change of methyl orange absorbance with concentration to obtain the methyl orange concentration corresponding to the corresponding absorbance. The adsorption efficiency of PAM / COF composite material for methyl orange at 20°C was calculated according to the above formula (1). The temperature of oscillation adsorption was adjusted to 25°C, 30°C, and 40°C, respectively. The adsorption efficiency of PAM / COF composite material for methyl orange at 25°C, 30°C, and 40°C was tested in the same way. The adsorption efficiency was taken as the ordinate and the adsorption time was taken as the abscissa, as shown in the figure. Figure 4 As shown in the figure, the adsorption performance of PAM / COF composite materials on methyl orange increases with increasing temperature, but the effects are similar between 25℃, 30℃ and 40℃, which shows that PAM / COF composite materials can effectively adsorb methyl orange at different temperatures and are particularly suitable for application in industrial wastewater treatment. Adsorption treatment can be carried out at 25~30℃ to achieve higher adsorption efficiency while reducing energy consumption and extending the service life of the material.

[0040] (III) Comparison of adsorption effects of PAM / COF composites on methyl orange aqueous solutions with different pH values A certain volume of methyl orange aqueous solution with pH values ​​of 3, 5, 7, 9, and 11 (the concentration of methyl orange aqueous solution is 30 mg / L), 50 mL of methyl orange aqueous solution with each pH value was taken as adsorption solution, 15 mg of PAM / COF composite material was added to each adsorption solution, and the solution was placed in a constant temperature oscillator at 30°C for oscillation adsorption. A certain amount of solution was taken at regular intervals, and the supernatant was taken after centrifugation to test the absorbance of the solution with a TU-1901 UV-visible photometer. The absorbance was substituted into the standard curve equation of the change of methyl orange absorbance with concentration to obtain the methyl orange concentration corresponding to the corresponding absorbance. The adsorption efficiency of the PAM / COF composite material on the methyl orange aqueous solution at different times was calculated according to the above formula (1). The adsorption efficiency was used as the ordinate and the adsorption time was used as the abscissa to draw a graph, as shown in FIG. Figure 5 As shown. It can be seen that the adsorption efficiency of PAM / COF composite materials for methyl orange increases with the increase of pH, especially under alkaline conditions, the adsorption effect is the best. This is because under alkaline conditions, the surface of the material carries more negative charges, and the electrostatic attraction between the material and the methyl orange molecules is enhanced, thereby improving the adsorption efficiency. Therefore, in practical applications, it is best to carry out adsorption under the condition of pH = 7 ~ 9 to obtain the best treatment effect and economy.

[0041] 4. Comparison of adsorption effects of PAM / COF composites on aqueous solutions of different dyes Prepare 50 mL of 30 mg / L methyl orange aqueous solution, Congo red aqueous solution, methylene blue aqueous solution, and crystal violet aqueous solution, respectively. Add 15 mg of PAM / COF composite material to each dye aqueous solution, place it in a constant temperature oscillator at 30°C for oscillation adsorption, take a certain amount of solution at a certain time interval, take the supernatant after centrifugation, and use TU-1901 UV-visible photometer to test the absorbance of the solution. Substitute the absorbance into the standard curve equation of methyl orange absorbance versus concentration to obtain the methyl orange concentration corresponding to the corresponding absorbance. Calculate the adsorption efficiency of PAM / COF composite material on different dye aqueous solutions at different times according to the above formula (1). Plot the adsorption efficiency as the ordinate and the adsorption time as the abscissa, as shown in the figure. Figure 6 As shown. It can be seen that the PAM / COF composite material shows excellent adsorption effects when treating different dyes, especially the best adsorption effects on methyl orange and Congo red, and the adsorption efficiency reaches more than 90% at 180 min. This may be attributed to the porous structure of COF in the material and the polar functional groups of PAM, which can effectively interact with these dye molecules. In contrast, the adsorption efficiency for methylene blue and crystal violet is slightly lower, but at 180 min, the adsorption efficiency for methylene blue and crystal violet also reaches more than 85%. It shows that the PAM / COF composite material prepared by the present invention has excellent adsorption effects on different dyes.

[0042] (V) Stability test of PAM / COF composite material on adsorption of methyl orange aqueous solution 15 mg of the PAM / COF composite material prepared in step (5) of Example 1 was weighed and placed in a beaker. 50 mL of a methyl orange aqueous solution with a pH of 9 and a concentration of 30 mg / L was added to the beaker. The mixture was placed in a constant temperature oscillator for oscillation adsorption at room temperature. The adsorption time was set to 120 min. After completion, a certain amount of the solution was taken, and the supernatant was taken after centrifugation. The absorbance was tested using a TU-1901 UV-visible photometer. The absorbance was substituted into the standard curve equation of the change of methyl orange absorbance with concentration to obtain the methyl orange concentration corresponding to the corresponding absorbance. The adsorption efficiency of the PAM / COF composite material for methyl orange was calculated according to formula (1). The PAM / COF composite material that has adsorbed methyl orange was added to a 5% sodium hydroxide solution, placed in a constant temperature oscillator at 40°C for 30 min for desorption, filtered after desorption, and the filtered adsorbent material was washed several times with distilled water until the washing liquid was neutral, then filtered again. The filtered adsorbent material was placed in an oven for drying and then used again for adsorption experiments. It was recycled for a total of 5 times, and the adsorption efficiency of the PAM / COF composite material for methyl orange after each adsorption was calculated. Plot the adsorption efficiency against the number of uses, as shown in Figure 2. Figure 7 It can be seen that after the PAM / COF composite material was recycled for 5 times, the adsorption efficiency of methyl orange was still stable at more than 80%, indicating that the PAM / COF composite material has good renewability and durability as an adsorption material for treating methyl orange wastewater. This shows that the PAM / COF composite material is not only structurally stable, but also can be reused many times, thus reducing the cost of wastewater treatment and has great application potential in actual dye wastewater treatment.

[0043] The PAM / COF composite material prepared by the present invention has good mechanical strength and chemical stability, overcomes the defect of poor mechanical properties of COF materials, and enhances the overall adsorption performance of the composite material. The adsorption effect on methyl orange dye wastewater is remarkable. In a wide pH range (such as from acidic to neutral) and at different temperatures (such as normal temperature to high temperature conditions), the PAM / COF composite material can maintain excellent adsorption capacity, is less affected by environmental conditions, and improves its applicability in practical applications. At the same time, it also shows good adsorption performance for other common dyes (such as methylene blue, Congo red, etc.). Therefore, the PAM / COF composite material prepared by the present invention is suitable for treating various types of dye wastewater and has broad application prospects in industrial fields such as textiles and printing and dyeing. At the same time, the PAM / COF composite material can achieve the regeneration of the adsorption material by simple alkali solution washing, the regeneration operation is convenient, the material consumption and cost are reduced, and the economic benefits are improved. The efficient adsorption capacity of the PAM / COF composite material can accelerate the wastewater treatment speed, improve the treatment efficiency, and enhance the economic benefits of the entire wastewater treatment process.

[0044] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made to the above embodiments by any technician familiar with the profession according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a PAM / COF composite material for treating dye wastewater, characterized in that The following steps are involved: (1) Weigh a certain amount of p-toluenesulfonic acid monohydrate and trialdehyde phloroglucinol, add them to deionized water, and ultrasonically vibrate for 10-20 min to obtain a mixed solution A; (2) Taking a certain volume of deionized water, add acrylamide, N,N-methylenebisacrylamide, polyvinyl pyrrolidone, PEG-200 polyethylene glycol and Tween 20 in sequence, and disperse by ultrasonic until the mixture is completely dispersed to obtain an aqueous phase; (3) mixing benzene, n-heptane and cyclohexane in a volume ratio of 1:1:2.5 and stirring well to obtain an oil phase; (4) According to the volume ratio of water phase to oil phase of 2:1, a certain amount of water phase prepared in step (2) and oil phase prepared in step (3) are taken, and the oil phase is added to the water phase while stirring. After the oil phase is completely added, stirring is continued until a milky white oil-in-water emulsion is formed, and ammonium persulfate is added to the oil-in-water emulsion. After stirring, the mixture is transferred to a polytetrafluoroethylene-lined reactor, and N,N,N',N'-tetramethylethylenediamine is dropped into the polytetrafluoroethylene-lined reactor, and the mixture is quickly stirred. The polytetrafluoroethylene-lined reactor is then sealed and placed in an oven at 55°C for reaction for 8 to 20 min. After the reaction is completed, the obtained product is centrifuged and washed three times with methanol, and then the centrifuged product is dried in a vacuum oven at 50°C for 8 to 12 h to obtain a porous polyacrylamide powder, which is recorded as PAM powder; (5) Adding PAM powder to the mixed solution A of step (1) and stirring evenly to obtain a mixed solution B; adding diaminoanthraquinone to the mixed solution B, stirring evenly and transferring the mixture to a polytetrafluoroethylene-lined reactor, heating the polytetrafluoroethylene-lined reactor at 120° C. for 18 h to fully react the mixture, and after the reaction is completed, naturally cooling the product to room temperature and then vacuum drying the product to obtain a porous polyacrylamide / COF composite material, referred to as a PAM / COF composite material.

2. The method for preparing the PAM / COF composite material for treating dye wastewater according to claim 1, characterized in that In step (1), the mass ratio of p-toluenesulfonic acid monohydrate to trialdehyde phloroglucinol is 22:5, and the ratio of the volume of deionized water to the total mass of p-toluenesulfonic acid monohydrate and trialdehyde phloroglucinol is 8 mL:27 mg.

3. The method for preparing the PAM / COF composite material for treating dye wastewater according to claim 1 or 2, characterized in that In step (2), the mass ratio of acrylamide, N,N-methylenebisacrylamide, polyvinyl pyrrolidone, PEG-200 polyethylene glycol, and Tween 20 is 13:1:1:1.2:8; the volume ratio of deionized water in step (2) to the volume ratio of deionized water in step (1) is 1:

1.

4. The method for preparing the PAM / COF composite material for treating dye wastewater according to claim 1, characterized in that The stirring speed in step (4) is 1500 rpm.

5. The method for preparing the PAM / COF composite material for treating dye wastewater according to claim 1, characterized in that In step (4), the concentration of ammonium persulfate in the oil-in-water emulsion is 1.25 mg / mL, and the volume ratio of N,N,N',N'-tetramethylethylenediamine to the oil-in-water emulsion is 1:

120.

6. The method for preparing the PAM / COF composite material for treating dye wastewater according to claim 1 or 2, characterized in that The mass ratio of diaminoanthraquinone in step (5) to trialdehyde phloroglucinol in step (1) is 3:

5.

7. The method for preparing the PAM / COF composite material for treating dye wastewater according to claim 1, characterized in that The PAM powder prepared in step (4) is a nearly spherical particle with a particle size of 300-600 μm. In the PAM / COF composite material prepared in step (5), the COF material is attached to the pore structure of the PAM material, and the particle size of the COF material is 50-200 nm.

8. Use of the PAM / COF composite material obtained by the preparation method as claimed in claim 1 in treating dye wastewater.

9. The use according to claim 8, characterized in that The concentration of dye wastewater is 30~50 mg / L, and the volume ratio of the added mass of PAM / COF composite material to the dye wastewater is 3 mg: 10 mL.

10. The use according to claim 8, characterized in that The pH of dye wastewater is greater than 7, and the adsorption equilibrium time of PAM / COF composite material for dye wastewater is 100~120 min.

Citation Information

Patent Citations

  • Covalent organic framework membrane with high rejection rate as well as raw material composition and preparation method thereof

    CN112808006A

  • Phase-change material taking MOFs as carrier and preparation method of phase-change material

    CN115058231A

  • Beta-cyclodextrin-polyacrylamide hydrogel based on covalent organic framework as well as preparation method and application of beta-cyclodextrin-polyacrylamide hydrogel

    CN116082573A

  • Chitosan-polyacrylamide composite porous hydrogel, preparation and use thereof, and metal ion-detecting reagent and method

    US20230147119A1